Stability of Measures of Pain Catastrophizing and Widespread Pain Following Total Knee Replacement. Issue 8 (11th June 2020) - Lape, Emma C.; Selzer, Faith; Collins, Jamie E.; Losina, Elena; Katz, Jeffrey N.
Abstract : Objective: Pain catastrophizing and widespread pain are predictors of pain chronicity/severity. Gaps remain in our understanding of the extent to which each is a stable (trait) or dynamic (state) variable. We undertook this study to assess the stability of each variable from before to after total knee replacement (TKR) and whether changes are explained by pain improvements. Methods: We used data from a prospective study of TKR recipients ages ≥40 years. Questionnaires included body pain diagrams assessing widespread pain, the Pain Catastrophizing Scale (PCS), and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale. We divided subjects into widespread pain groups (0 versus 1–2 versus ≥3 pain regions) and into low and high PCS score groups (<16 versus ≥16). We assessed changes in group membership from pre‐TKR to 12 months post‐TKR, then compared these changes between subjects with most and least WOMAC pain improvement. Results: A total of 176 subjects completed scales at both time points; 64% were female, the mean age was 66 years, and baseline median WOMAC pain score was 40. In all, 71% of subjects in the high PCS score group improved to join the low PCS score group at follow‐up. While 73 subjects (41%) changed widespread pain group, they were similarly likely to worsen and to improve. We found a statistically significant positive association of improvement in WOMAC pain score with improvement in PCS score (r = 0.31), but not widespread pain (r = –0.004). Conclusion: The PCS score reflects state‐like aspects of catastrophizing that diminish along with pain. In contrast, widespread pain scores worsened and improved equally often, regardless of knee pain relief. The findings urge caution in interpreting PCS score and widespread pain as trait measures in musculoskeletal research.